2008
DOI: 10.1007/s11096-008-9221-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication use in the child and adolescent psychiatry wards of a French hospital

Abstract: The extensive use of drugs for off-label indications in children and adolescents suggests that prospective post-marketing studies should be carried out to evaluate efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
4
15
0
3
Order By: Relevance
“…Off-label prescription also varied with respect to dosage, indication, route of administration and therapeutic group [1][2][3]. Analgesics (paracetamol, ketoprofen, thiopental, fentanyl), bronchodilators (budesonide and salbutamol) and psychotropic drugs were among those medicines most frequently prescribed offlabel across countries [7][8][9][10]. Very few studies have examined the contribution of medicines used in children in an off-label or unlicensed manner to ADR occurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Off-label prescription also varied with respect to dosage, indication, route of administration and therapeutic group [1][2][3]. Analgesics (paracetamol, ketoprofen, thiopental, fentanyl), bronchodilators (budesonide and salbutamol) and psychotropic drugs were among those medicines most frequently prescribed offlabel across countries [7][8][9][10]. Very few studies have examined the contribution of medicines used in children in an off-label or unlicensed manner to ADR occurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…8 In inpatients, Winterfeld et al 9 reported, in 2 children and adolescent inpatient units in France, that 90% of the AP prescriptions were off-label for diagnoses such as schizophrenia, anxiety disorders, and ADHD/DBDs. In a prospective study of psychotropic medications conducted in a French pediatric hospital during 6 months, 69% off-label AP prescription was described.…”
mentioning
confidence: 99%
“…8 In both studies, risperidone was the most common off-label prescribed drug, 31% and 12%, respectively. 8,9 Specifically, risperidone was the SGA most prescribed in almost all studies on the prevalence of prescriptions in children and adolescents 7,10 as well as in an adolescent inpatient setting, 11 with the exception of 1 study performed in Italy. 12 Moreover, in a prospective study of child and adolescent first episode of psychosis patients (Child and Adolescent First Episode of Psychosis Study), risperidone was the most used AP in nonaffective psychotic patients, whereas olanzapine and quetiapine were more prescribed than risperidone for affective psychosis.…”
mentioning
confidence: 99%
“…However, successful treatment demands a diagnosis and medication use, as well as precise indications. In addition, official indications for the most commonly used psychotropic medications in children are not officially established, and off-label prescriptions have quickly expanded across the world during the past decade [32][33][34] . This expansion could be related to the fact that in many cases the prescription does not come from a specialist but rather from a general physician and is based on a lack of relevant assessment and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the study population received stimulant treatment. This can be compared to other countries such as the United States and France, where the overall psychotropic use is 70.7% and 46%, respectively, and antipsychotics are the most frequently used psychotropic medication class (44%) [16,24,32] . Others studies have reported that the most frequently used paediatric psychotropics are antidepressants, selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine and sertraline, and stimulants [13,24,36,37] .…”
Section: Discussionmentioning
confidence: 99%